Evaluation Of Information Sources : A Study Of Sarawakian Business-To-Business Elite Managers - Ernest Cyril, de Run; Siti Hasnah, Hassan (Journal of Asia Pacific Marketing, 2003)
This paper reports the findings of an empirical study on the information behavior of 179 SME elite managers based in Sarawak, Malaysia. The purpose of the paper was to make available its findings for marketing managers to develop an appropriate promotion strategy that would reach such elite managers. This paper details SME elite managers ranking of important, reliable and most often used information sources by industry, equity and overall. The paper also notes the difference in personal and impersonal information sources importance, reliability and use by industry, equity and overall…